Teaching Listening Through Podcast - Retno Rahayuningsih; Yanti Rosalinah; Ibnu Subroto (LPPM Universitas Bina Sarana Informatika, 2021)
Listening is one of the skills in teaching English. Listening is not passive ability but active communication. Listening aims to understand and respond to what we hear. When we hear, we always give response either through direct spoken language or body language. To get maximum results, teachers must be able to use media that can facilitate and motivate students in the learning process of hearing. In this case, the media that is currently being used is podcast audio. Podcasts come from the words